2010
DOI: 10.3150/09-bej236
|View full text |Cite
|
Sign up to set email alerts
|

Tightness for the interface of the one-dimensional contact process

Abstract: We consider a symmetric, finite-range contact process with two types of infection; both have the same (supercritical) infection rate and heal at rate 1, but sites infected by Infection 1 are immune to Infection 2. We take the initial configuration where sites in $(-\infty,0]$ have Infection 1 and sites in $[1,\infty)$ have Infection 2, then consider the process $\rho_t$ defined as the size of the interface area between the two infections at time $t$. We show that the distribution of $\rho_t$ is tight, thus pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…(2.8) (In Lemma 2.6(i) of [2] it is shown that a vertex x satisfies certain properties in the Harris system with positive probability, and then Proposition 2.7(i) and (iii) of [2] imply that a vertex satisfying the mentioned list of properties isβ-insulating in the sense that we give here. Property (2.8) above can be obtained from Lemma 2.6(ii) of [2] through a routine argument that we will omit). The constantsβ andδ of the above proposition will be fixed throughout the paper.…”
Section: Insulating Pointsmentioning
confidence: 91%
See 2 more Smart Citations
“…(2.8) (In Lemma 2.6(i) of [2] it is shown that a vertex x satisfies certain properties in the Harris system with positive probability, and then Proposition 2.7(i) and (iii) of [2] imply that a vertex satisfying the mentioned list of properties isβ-insulating in the sense that we give here. Property (2.8) above can be obtained from Lemma 2.6(ii) of [2] through a routine argument that we will omit). The constantsβ andδ of the above proposition will be fixed throughout the paper.…”
Section: Insulating Pointsmentioning
confidence: 91%
“…In case x is β-insulating, the cone {y ∈ Z : x − βt ≤ y ≤ x + βt} is called a descendancy barrier. In [13] and [2], it was shown by the following proposition. ∀ε > 0 ∃n : ∀A ⊂ Z with #A ≥ n, P(no point of A isβ-insulating) < ε.…”
Section: Insulating Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…We remark that interface tightness is a fairly common phenomenon among many onedimensional interacting particle systems. Other models for which this has been proved include one-dimensional two-type contact processes with strong bias (in the sense that one type can overtake the other, but not vice versa) [AMPV10], or no bias (no type can infect a site occupied by the other type) [Val10,MV16], as well as one-dimensional asymmetric exclusion processes that admit so-called blocking measures (see e.g. [BM02,BLM02]).…”
Section: Introduction 1interface Tightnessmentioning
confidence: 99%
“…with § 2.2, p. 913 ff., Andjel et.al. [AMPV10]. The special case of the analog of Theorem 1 for the so-called basic case (i.e.…”
mentioning
confidence: 99%